Pelayanan Publik Berbasis Collaborative Governance Di Pelabuhan Andi Mattalata Kabupaten Barru - Jum Harianto Fatman; Nurlinah Nurlinah; Suhardiman Syamsu (Kolaborasi : Jurnal Administrasi Publik, 2023)
This study aims to describe collaborative governance-based public services at Andi Mattalata Port, Barru Regency. This type of research uses a descriptive research type in order to provide an overview of qualitative research data. This research focuses on how to describe the collaboration of stakeholders at Andi Mattalata port. This study used several methods, namely interviews, observation and documentation as techniques in data collection. The results of this study provide an explanation of the theory of Ansell and Gash in (Wibowo, 2020) put forward several stages for measuring, namely a) Face to Face; b) Trust Building; c) Commitment to Processes; d) Share Understanding; e) Intermediate Outcomes. Technical constraints occur because the initial commitment process did not go well resulting from being inconsistent with the initial face-to-face talks which hindered the continuation of cooperation between stakeholders who work together in carrying out passenger and freight services, but this can be minimized by emotional factors that occur by the parties working together so that the service can run even though it is not optimal.